International Chinese students’ experiences of participating in mandala-based art therapy in Korea: a phenomenological study - Mo, Ya Nan; Ko, Kyung Soon (Frontiers in Psychology, 2023)
Background: Although China and South Korea share a similar East Asian culture, owing to major social and cultural differences, international students encounter several difficulties, which can lead to various psychological problems. Objective: To explore the experiences of eight Chinese doctoral students in South Korea participating in mandala-based art therapy. Method: Data for this phenomenological study were gathered through individual interviews and visual art from April 5 to 20, 2022. The MAXQDA software program was used for data analysis. Results: The data analysis results yielded 355 codes, 53 subcategories, and 17 categories. Five final themes emerged: (a) sealed lips by others' eyes, (b) inner exploration and outward expression, (c) healing power of the mandala, (d) filling the inner space together, and (e) opportunities to understand art therapy. Conclusion: The researchers hope that completing this intervention will enable participants to complete their studies more effectively and achieve their ideals as well as future career goals, helping them ultimately return home safely with both personal and academic growth.